2016
DOI: 10.1016/j.biomaterials.2016.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Polyplex-mediated inhibition of chemokine receptor CXCR4 and chromatin-remodeling enzyme NCOA3 impedes pancreatic cancer progression and metastasis

Abstract: Pancreatic cancer (PC) is one of the most aggressive malignancies due to intense desmoplasia, extreme hypoxia and inherent chemoresistance. Studies have implicated the expression of chemokine receptor CXCR4 and nuclear receptor co-activator-3 (NCOA3) in the development of desmoplasia and metastatic spread of PC. Using a series of polymeric CXCR4 antagonists (PCX), we optimized formulation of PCX/siNCOA3 polyplexes to simultaneously target CXCR4 and NCOA3 in PC. Cholesterol-modified PCX showed maximum CXCR4 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 59 publications
2
32
0
Order By: Relevance
“…[15,17] Briefly, a Boc-protected CX (76.3 mg, 0.1 mmol) and HMBA (22.4 mg, 0.1 mmol) were reacted in dark under nitrogen protection in methanol/water (7/3 v/v) for 14 days at 50°C. [15,17] Briefly, a Boc-protected CX (76.3 mg, 0.1 mmol) and HMBA (22.4 mg, 0.1 mmol) were reacted in dark under nitrogen protection in methanol/water (7/3 v/v) for 14 days at 50°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[15,17] Briefly, a Boc-protected CX (76.3 mg, 0.1 mmol) and HMBA (22.4 mg, 0.1 mmol) were reacted in dark under nitrogen protection in methanol/water (7/3 v/v) for 14 days at 50°C. [15,17] Briefly, a Boc-protected CX (76.3 mg, 0.1 mmol) and HMBA (22.4 mg, 0.1 mmol) were reacted in dark under nitrogen protection in methanol/water (7/3 v/v) for 14 days at 50°C.…”
Section: Methodsmentioning
confidence: 99%
“…Initial cytotoxicity of the synthesized polymers was evaluated by a cell viability assay in mouse fibroblasts L929 ( Figure 1F). [17] Compared with the (F-)PCX polyplexes, formation of nanoemulsion with PFC through fluorine-fluorine interactions increased the stability of the emulsion polyplexes ( Figure S2, Supporting Information). Initial in vivo toxicity testing using the lactate dehydrogenase (LDH) assay in bronchoalveolar lavage fluid (BALF) of healthy mice revealed that all PCX-based formulations were significantly less toxic than control PEI polyplexes ( Figure S1, Supporting Information).…”
Section: Preparation and Characterization Of F-pcx@pfc Nanoemulsionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated that MUC4 expression can be indirectly downregulated by silencing NCOA3, one of the master regulators of MUC4 and other mucins [68] using retroviral shRNA vector. More importantly, our subsequent studies demonstrated the feasibility of downregulating MUC4 expression in established tumors by delivering NCOA3-directed siRNA oligonucleotides polyplexed with tumor-targeted polymeric CXCR4 antagonist [76]. A combination of CXCR4 inhibition and NCOA3 silencing in orthotopic tumors resulted in reduced tumor growth, decreased metastasis, and enhanced perfusion along with a marked decrease in the expression of MUC4 [76].…”
Section: Muc4-based Therapeutic Approaches In Pdacmentioning
confidence: 99%
“…However, the manufacturing complexity and unsatisfactory drug loading ability of the traditional nanoparticles remain a significant hurdle for their clinical translation. Alternative approaches from our lab have utilized pharmacologically active nanoparticles based on polymeric drugs and prodrugs to achieve delivery of drug/siRNA, drug/miRNA, and drug/DNA combinations [1214]. When properly designed, such polymeric drug nanoparticles have several advantages, including simple production and high drug contents that makes them suitable for clinical translation.…”
Section: Introductionmentioning
confidence: 99%